Chromosome-scale assembly uncovers genomic compartmentation of Fusarium oxysporum f. sp. albedinis, the causal agent of Bayoud disease in date palm - Khayi, Slimane; Armitage, Andrew D.; Gaboun, Fatima; Meftah-kadmiri, Issam; Lahlali, Rachid; Fokar, Mohamed; Mentag, Rachid (Frontiers in Microbiology, 2023)
Date palm (Phoenix dactylifera) is the most significant crop across North Africa and the Middle East. However, the crop faces a severe threat from Bayoud disease caused by the fungal pathogen Fusarium oxysporum f. sp. albedinis (FOA). FOA is a soil-borne fungus that infects the roots and vascular system of date palms, leading to widespread destruction of date palm plantations in North Africa over the last century. This is considered the most devastating pathogen of oasis agriculture in North Africa and responsible for loss of 13 million trees in Algeria and Morocco alone.